Wages Boards in Australia: II. Boards Outside Victoria. III. Organization and Procedure - Hammond, M. B. (Quarterly Journal of Economics, 1915)
II. Boards outside Victoria. 1. South Australia, 326. — 2. Queensland, 332. — 3. New South Wales, 334. — 4. Tasmania, 337.— III. Organization and Procedure. 1. Organization and Appointment, 339. — Grouping of trades, multiplication of boards, 341. — Number of members, 341. — Women, 342. — Chairmen, 343. — "Award" or "determination, " 344. — Court of Industrial Appeals in Victoria; of Industrial Arbitration elsewhere, 346. — 2. Wages Boards at work, 347. — Importance of chairman, 350. — Real or apparent waste of time, 353. — Informal proceedings, 355. — Absence of any guiding principle, 356. — Cost of living a conspicuous factor, 357. — In Victoria, true examples of collective bargaining; elsewhere, less so, 360.